EMOTIONAL LEADERSHIP STYLE AND ITS ROLE IN MOTIVATING TEACHERS AND STUDENTS: EMOTIONAL LEADERSHIP STYLE AND ITS ROLE IN MOTIVATING TEACHERS AND STUDENTS - Saipul Anwar Anwar; Sukirman Sukirman; Muhammad Sirozi (LP2M IAIN Sultan Amai Gorontalo, 2026)
Abstract Leadership is a fundamental factor in determining the success of educational institutions, particularly in creating a productive, harmonious, and quality-oriented work environment. In the context of modern educational management, leadership effectiveness is not only determined by intellectual intelligence but also by the ability to manage and express emotions positively, known as emotional intelligence. This study aims to describe the concept of emotional leadership in educational management, analyze the role of leaders’ emotional intelligence in motivating teachers and students, and examine the Islamic perspective on emotional leadership as a model grounded in moral and spiritual values. The research was conducted at SD Negeri 42 Talang Ubi, Penukal Abab Lematang Ilir Regency, using a qualitative approach through library research and descriptive analysis of relevant empirical and conceptual sources. The findings reveal that emotional intelligence–based leadership significantly influences teachers’ motivation, loyalty, and professionalism, while fostering a conducive, harmonious, and humanistic school climate. From the Islamic perspective, emotional leadership aligns with the exemplary leadership of Prophet Muhammad ﷺ, who demonstrated a balance of gentleness, empathy, and moral firmness. This principle remains relevant in the modern educational era, which demands the integration of emotional intelligence and spirituality in leadership. Therefore, emotional intelligence–based leadership is not only a managerial necessity but also a manifestation of Islamic ethical and moral values in building a character-based educational culture. Keywords: emotional leadership, emotional intelligence, teacher motivation, Islamic perspective